Debate on Global Urbanisms and the Nature of Urban Theory. (21st December 2015) - Robinson, Jennifer; Roy, Ananya
Abstract: Urban studies is undergoing a phase of rich experimentation, with a proliferation of paradigms and exploration or invention of various methodologies inspired by the diversity and shifting geographies of global urbanization. In particular, there has been an effort to rethink the Euro–American legacy of urban studies and consider the relational multiplicities, diverse histories and dynamic connectivities of global urbanisms. Such a task is especially important at a time when significant urban transformations are underway in the global South. From the remaking of the developmental state at the urban scale to fierce struggles over land, housing and urban services to ambitious visions of the world‐class city, these urban processes cannot be understood as simply a postscript to the urban transformations of the North Atlantic.